Author Correction: Colonial history and global economics distort our understanding of deep-time biodiversity (Nature Ecology & Evolution, (2021), 10.1038/s41559-021-01608-8) - Raja, Nussaïbah Begum; Dunne, Emma; Matiwane, Aviwe; Khan, Tasnuva Ming; Nätscher, Paulina; Ghilardi, Aline Marcele; Chattopadhyay, Devapriya (Nature Ecology & Evolution, 2022)
In the version of this article initially published, the designation “Central” America was omitted in an Extended Data Fig. 2c panel heading and the caption as well as in the Extended Data Fig. 3 caption. The figure and captions have been updated to clarify “Central and South America” in each instance.
CRIS-Team Scopus Importer:2022-02-11